POTENSI SUPLEMENTASI SMALL-QUANTITY LIPID-BASED NUTRIENT PRENATAL DAN POSTNATAL SEBAGAI PENCEGAHAN ANEMIA DEFISIENSI BESI PADA ANAK DI BAWAH USIA DUA TAHUN - Muhammad Yusuf; Arila Atalia; Avisa Cetta Cresma (Essence of Scientific Medical Journal, 2022)
Introduction: Iron Deficiency Anemia (IDA) is considered a public health problem in Indonesia. The main consequences of IDA in infants include increased risk of permanent cognitive and psychomotor impairments that can lead to decreased quality of life in adulthood. Recommendations for iron supplementation for pregnant women and infants have uncomfortable side effects leading to poor adherence. Small Quantity Lipid-Based Nutrient Supplement (SQ-LNS) was developed as a novel iron fortification approach for pregnant and lactating women and children. The objective of this literature review is to analyze the effectiveness of SQ-LNS supplementation to prevent IDA in infants under two years of age. Methods: A Literature review was constructed with PICOS criteria and the clinical trial data were extracted from “PUBMED”, “Cochrane”, and “Europe-PMC” databases, matching the inclusion criterias. Results and Discussion: 10 studies were included in the literature review. IDA biomarkers such as Hemoglobin, serum Ferritin, and soluble transferrin receptor (sTfR) were significantly better in the SQ-LNS groups compared to control. Thus, the prevalence of anemia, iron deficiency, and iron deficiency anemia were lower in the SQ-LNS groups compared to control. SQ-LNS also optimized the level of Hepcidin and enhanced the growth and development of infants, represented by higher length-for-age z scores, weight-for-age z scores, locomotor development scores, and lower prevalence of stunting. Conclusion: SQ-LNS supplementation for pregnant women, nursing mothers, and children under two years of age has the potential to optimize Hb levels, serum Ferritin, sTfR, as well as prevent IDA in children and support child growth and development.